Atividade da lactato desidrogenase como método para classificação e identificação de efusões neoplásicas em líquidos pleurais e peritoneais de cães e gatos - Barbosa, Nathália Viana (2022)
The analysis of effusions is extremely important for the best clinical guidance. Previous studies showed good results with the measurement of lactate dehydrogenase (LDH) activity in the classification of human and animal effusions, in addition to demonstrating its use in the diagnosing of cancer patients. Therefore, this study aimed to evaluate the activity of LDH and the concentration of total proteins (TP) in serum and in the pleural and peritoneal effusions of dogs and cats treated at the Hospital Veterinário Universitário (HVU) of the Universidade Federal de Santa Maria (UFSM) with in order to demonstrate its use in the classification of effusions and to investigate the activity of LDH for the diagnosis of neoplasms. For this, 67 effusion samples were analyzed, along with the patients' serum samples, for LDH activity and TP concentration. Effusions were organized into groups GI (low protein transudate), GII (high protein transudate), and GIII (exudate) according to the conventional classification and, simultaneously, distributed into groups GPN (possibly neoplastic etiopathogenesis) and GAN (non neoplastic disease) without discrimination of species. Differences in TP concentrations and LDH activity in effusion and effusion LDH/serum LDH (LDHR) and effusion TP/serum TP (TPR) ratios were observed between the three groups of dogs and when comparing groups GI/GII and GI/GIII. Groups GII/GIII only differed when considering the parameters LDH activity in effusion and LDHR. Effusions possibly caused by neoplasms showed higher values of LDH activity in the effusion when compared to non-neoplastic effusions. Furthermore, the samples were organized into groups according to the mechanism attributed by the clinicians as the cause of the effusion: IHP (increased hydrostatic pressure), DOP (decreased oncotic pressure), HEM (hemorrhage), SEP (bacterial infection), NEO (neoplasm) and NS (neoplasm associated with bacterial infection). Considering the etiopathogenesis of effusions in dogs and cats, differences were observed between groups for serum TP, effusion TP, effusion LDH, TPR and LDHR. For the parameters LDH activity in effusion and TPR, there was a discrepancy between the DOP/NEO, DOP/SEP, DOP/NS, IHP/SEP, and DOP/HEM groups. Likewise, a disparity was identified between DOP/SEP, DOP/NS, and IHP/SEP in the values of the LDHR and, between DOP/NEO, DOP/SEP, and DOP/HEM in the concentrations of TP in the body cavity fluids. Based on the clinical diagnosis, Light's criteria used to classify human cavity fluids showed greater sensitivity in the determination of transudates and exudates, and greater specificity in identifying transudates, when compared to the conventional classification. Despite the low number of samples involved, this study corroborates the correlation of the biochemical analyzes tested with the conventional classification proposed for dogs. The differences observed between groups according to the mechanism of formation of the cavity fluid support the hypothesis that these analyzes may be effective for classifying effusions in dogs and cats. With the results obtained, it is possible to propose the use of LDH activity in effusions as a complementary test in the diagnosis of cavity neoplasms, especially in cases in which the cytological analysis of the cavity fluid is inconclusive, providing an immediate clinical approach to the patient.